Etiology of Upper Gastrointestinal Haemorrhage in a Teaching Hospital - Ahmed, M Uddin; Ahad, M Abdul; Alim, MA; Ekram, ARM Saifuddin; Masum, Q Abdullah Al; Tanu, Sumona; Uddin, Refaz (TAJ: Journal of Teachers Association, 2009)
A descriptive study on all cases of haematemesis and or melaena was carried out at Rajshahi Medical College Hospital to observe the demographic profile, clinical presentation, cause and outcome of upper gastrointestinal bleeding in a tertiary hospital of Bangladesh. Fifty adult patients presenting with haematemesis and or melaena admitted consecutively into medical unit were evaluated through proper history taking, thorough clinical examination, endoscopic examination with in 48 hours of first presentation and other related investigations. Patients those who were not stabilized haemodynamically with in 48 hours of resuscitation and endoscopy could not be done with in that period were excluded from this study. Results our results showed that out of 50 patients 44 were male and 6 were female and average age of the patients was 39.9 years. Most of the patients were from low socio-economic condition. Farmers, service holders and laborers were the most (57%) affected group. Haematemesis and melaena (42%), only melaena (42%) and only haematemesis (16%) were the presenting features. Endoscopy revealed that duodenal ulcer (34%) was the most common cause of UGI bleeding followed by rupture of portal varices (16%) , neoplasm (10%) , gastric ulcer (08%) and gastric erosion (06%). Acute upper GI bleeding is a common medical problem that is responsible for significant morbidity and mortality. The extensive clinical spectrum of gastrointestinal bleeding may encompass many different clinical scenarios. It is often very difficult to find out the cause and site of bleeding. We find that though cases of ruptured oesophageal varices were increasing, still peptic ulcer disease is the leading cause of haematemesis and melaena. doi: 10.3329/taj.v21i1.3220 TAJ 2008; 21(1): 53-57